Forging Alliances in Interdisciplinary Rehabilitation Research (FAIRR): A Logic Model. (July 2017) - Gill, Simone V.; Khetani, Mary A.; Yinusa-Nyahkoon, Leanne; McManus, Beth; Gardiner, Paula M.; Tickle-Degnen, Linda
Abstract : Abstract: In a patient-centered care era, rehabilitation can benefit from researcher-clinician collaboration to effectively and efficiently produce the interdisciplinary science that is needed to improve patient-centered outcomes. The authors propose the use of the Forging Alliances in Interdisciplinary Rehabilitation Research (FAIRR) logic model to provide guidance to rehabilitation scientists and clinicians who are committed to growing their involvement in interdisciplinary rehabilitation research. We describe the importance and key characteristics of the FAIRR model for conducting interdisciplinary rehabilitation research. Abstract : Supplemental digital content is available in the text.